Pregnancy despite ovarian insufficiency in a patient with breast cancer. (19th July 2012) - Mahany, Erica B.; Hershman, Dawn L.; Sauer, Mark V.; Choi, Janet M.
Abstract: Future fertility is a concern for many young breast cancer survivors. Secondary amenorrhea occurs frequently during or soon after oncologic treatment. Return of menstruation and serum biomarkers are not absolute predictors of future fertility. We report a case of a 28 year old gravida 0 with recurrent Stage IIB invasive ductal breast carcinoma who managed to conceive twice despite showing clinical and biochemical signs of decreased ovarian reserve following treatment with chemotherapy and radiation. This case illustrates the potential for fertility in a patient with breast cancer despite chemotherapy‐related amenorrhea and undetectable anti‐Müllerian hormone levels. It exemplifies the imprecise nature of all clinical tests used to predict future fertility in breast cancer patients post‐treatment. It should remind all providers to be careful in basing recommendations for childbearing on these surrogate endpoints.